Coconut Milk and Coconut Oil: Their Manufacture Associated with Protein Functionality. Issue 8 (13th July 2018) - Patil, Umesh; Benjakul, Soottawat
Abstract: Coconut palm ( Cocos nucifera L.) is an economic plant cultivated in tropical countries, mainly in the Asian region. Coconut fruit generally consists of 51.7% kernel, 9.8% water, and 38.5% shell. Coconut milk is commonly manufactured from grated coconut meat (kernel). Basically, coconut milk is an oil‐in‐water emulsion, stabilized by some proteins existing in the aqueous phase. Maximization of protein functionality as an emulsifier can enhance the coconut milk stability. In addition, some stabilizers have been added to ensure the coconut milk stability. However, destabilization of emulsion in coconut milk brings about the collapse of the emulsion, from which virgin coconut oil (VCO) can be obtained. Yield, characteristics, and properties of VCO are governed by the processes used for destabilizing coconut milk. VCO is considered to be a functional oil and is rich in medium chain fatty acids with health advantages.